2020
DOI: 10.3389/fpsyg.2020.00704
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effect of Goal Attainment and Goal Importance on Acculturation and Well-Being

Abstract: The purpose of the present research is to shed light on whether and when migrants' goal pursuit relates to their acculturation and well-being. Previous research has demonstrated the beneficial role of striving for and attaining intrinsic goals on well-being. Yet, the relationship between the pursuit of intrinsic goals and acculturation has hardly been addressed. To fill this void, we investigated whether migrants' acculturation and wellbeing can be seen as a function of their pursuit of intrinsic goals. We pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Only few studies investigated intrinsic goal importance and attainment simultaneously in the prediction of psychological functioning. These previous findings showed that intrinsic goal importance and attainment are moderately to highly correlated (e.g., Ryan et al, 1999 ; Sheldon & Krieger, 2014 ; Toth-Bos, 2020 ) and pointed consistently towards a more critical role for intrinsic goal attainment (compared to importance) in the prediction of subjective well-being (e.g., Kasser & Ryan, 2001 ; Sheldon & Krieger, 2014 ; Tóth et al, 2018 ). Besides the unique role of intrinsic goal importance and attainment, few studies have examined the possible interplay between these two concepts.…”
Section: How Do Late Adults Experience Meaning During the Covid-19 Lo...mentioning
confidence: 85%
“…Only few studies investigated intrinsic goal importance and attainment simultaneously in the prediction of psychological functioning. These previous findings showed that intrinsic goal importance and attainment are moderately to highly correlated (e.g., Ryan et al, 1999 ; Sheldon & Krieger, 2014 ; Toth-Bos, 2020 ) and pointed consistently towards a more critical role for intrinsic goal attainment (compared to importance) in the prediction of subjective well-being (e.g., Kasser & Ryan, 2001 ; Sheldon & Krieger, 2014 ; Tóth et al, 2018 ). Besides the unique role of intrinsic goal importance and attainment, few studies have examined the possible interplay between these two concepts.…”
Section: How Do Late Adults Experience Meaning During the Covid-19 Lo...mentioning
confidence: 85%
“…This large gap needs to be emphasized [ 28 ] and explored further because it indicates trainees’ greatest dissatisfaction with the occupational item. Attaining intrinsic goals, such as personal growth [ 38 , 39 ], is positively related to acculturation and life satisfaction and negatively related to anxiety and depression among the migrant population [ 40 ]. Supporting trainees to identify and accomplish their goals might support their acculturation and mental well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In developed societies, intrinsic and extrinsic goals respectively relate positively and negatively to well-being constructs. For example, in the US, UK, and Germany, preference for intrinsic goals over extrinsic goals was positively associated with subjective well-being and negatively associated with neurotic symptoms (Kim et al, 2003;Toth-Bos et al, 2020). Also, intrinsic goals were positively linked to well-being and negatively to ill-being in Canada (Hope et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%